2019
DOI: 10.7202/1060031ar
|View full text |Cite
|
Sign up to set email alerts
|

La performance sociétale des entreprises dans un contexte international : vers une convergence des modèles de capitalisme ?

Abstract: Notre étude cherche à évaluer, dans un cadre théorique articulant le champ politique de la RSE et l’analyse institutionnelle comparée, la performance sociétale des entreprises dans différents modèles de capitalisme. Elle vise à interroger l’hypothèse très discutée de la convergence des différents modèles vers un type libéral anglo-saxon, dans un contexte de globalisation économique et financière. Nos résultats montrent que les modèles de capitalisme libéral, européen continen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…This universalist vision of CSR may help to explain the multinational firms’ behavior in this domain, even though it has been corroborated by very few empirical studies (Jackson and Apostolakou, 2010; Igalens et al , 2008; Ho et al , 2012). In a recent study focused on the environmental, social and governance (ESG) performances characterizing post-crisis models of capitalism, Ben Larbi et al (2019) have demonstrated that this convergence dynamic is in fact only skin-deep and does not reflect the predominance of any particular model of capitalism. Even as the 2008 economic crisis destabilized the neo-liberal model by highlighting its dangers, it also helped to significantly advance collective awareness of the benefits of CSR, reflecting a general concern about the need for corrective measures and attesting to a political desire for self-regulation (Fernández and Souto, 2009; Den Hond et al , 2014), as observed in the 2008 post-crisis period, where finance needs restructuring to repair legitimacy (Wang, 2010).…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…This universalist vision of CSR may help to explain the multinational firms’ behavior in this domain, even though it has been corroborated by very few empirical studies (Jackson and Apostolakou, 2010; Igalens et al , 2008; Ho et al , 2012). In a recent study focused on the environmental, social and governance (ESG) performances characterizing post-crisis models of capitalism, Ben Larbi et al (2019) have demonstrated that this convergence dynamic is in fact only skin-deep and does not reflect the predominance of any particular model of capitalism. Even as the 2008 economic crisis destabilized the neo-liberal model by highlighting its dangers, it also helped to significantly advance collective awareness of the benefits of CSR, reflecting a general concern about the need for corrective measures and attesting to a political desire for self-regulation (Fernández and Souto, 2009; Den Hond et al , 2014), as observed in the 2008 post-crisis period, where finance needs restructuring to repair legitimacy (Wang, 2010).…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
“…The process of economic integration in Europe, the increasing liberalization of financial markets and the competitive pressure induced by the globalization of trade suggest that countries with liberal and coordinated market economies (referred hereafter as LMEs and CMEs) have been able to move toward convergence. However, fundamental social compromises, particularly with regard to corporate social responsibility (CSR) have not always been part of this convergence model (Ben Larbi et al , 2019), allowing debates in the literature concerning the reasons of its emergence and integration according to models of capitalism. Differences in CSR implementation could depend of the institutional or organizational levels (Aguinis and Glavas, 2012), political, labor, educational and cultural systems of each model of capitalism (Aguilera and Jackson, 2003; Ioannou and Serafeim, 2012).…”
Section: Introductionmentioning
confidence: 99%